Demonstration of isospecific free radical polymerization of acrylate controlled by conformation and chirality of monomer. Issue 17 (11th April 2015) - Tanaka, Hitoshi; Matsubara, Yoshitaka; Kusunoki, Katsuhiko; Saito, Naoki; Kibayashi, Tatsuya
ABSTRACT Radical polymerization of lactic acid‐based chiral and achiral methylene dioxolanones, a model for conformationally s‐cis locked acrylate, was carried out with AIBN to demonstrate an isospecific free radical polymerization controlled by chirality and conformation of monomer. Polymerization of the dioxolanones proceeded smoothly without ring opening to give a polymer with moderate molecular weight and 100% of maximum isotacticity. ESR spectrum indicated a twisted conformation of the growing poly(methylene dioxolanone) radical in contrast to an acyclic analogous radical, suggesting a restriction of the free rotation around main chain CαCβ bond of the growing radical center. Chirality as well as the polarity and bulkiness of monomer affected the polymer tacticity, and chiral alkyl substituent would afford a high isotactic polymer, in which higher the enantiomeric excess of the monomer was, higher the isotacticity of the polymer was. While, achiral or polar substituents including dibenzyl and trichloromethyl groups would afford an atactic polymer. In addition, glass transition temperature (Tg) of the resulting polymers was significantly high, ranging from 172.2 to 229.8 °C, and even for an isotactic polymer Tg was as high as 206.8 °C. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 2007–2016